2010
DOI: 10.1002/atr.142
|View full text |Cite
|
Sign up to set email alerts
|

Understanding members' carsharing (activity) persistency by using econometric model

Abstract: SUMMARYCarsharing is an innovative travel alternative that has recently experienced considerable growth and become part of sustainable transportation initiatives. Although carsharing is becoming increasingly a popular alternative transportation mode in North America, it is still an under-researched area. Current research is aimed at better understanding of the behavior of carsharing users. For every member, a two-stage approach microsimulates the probability of being active in any month using a binary probit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Morency et al also identified gender and age as characteristics having a significant impact on carsharing behaviour [18]. They also found out that user behavior in the previous four months directly influences the current frequency of usage.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Morency et al also identified gender and age as characteristics having a significant impact on carsharing behaviour [18]. They also found out that user behavior in the previous four months directly influences the current frequency of usage.…”
Section: Literature Reviewmentioning
confidence: 97%
“…For example, Morency et al analyzed carsharing transaction data without a location identifier and thus could not test neighborhood socio-economic and built environment variables [10]. With the data from the carsharing operator of Montreal, De Lorimier and El-Geneidy estimated a model that predicts the number of monthly hours-reserved per vehicle [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The one or two person household was mentioned as one of the characteristics of carsharing users [20] and later Celsor and Millard-Ball tested the percentage of "1-person households" [8]. The gender of carsharing users has been tested in several studies, revealing that males use carsharing services more frequently than females [10,28,29]. For this study, the average household size and percentage of male population are measured for each district and tested as an independent variable.…”
Section: Demographic-related Variablesmentioning
confidence: 99%
“…More recently, Shaheen et al (2009) looked back at the last decade of carsharing in North America, identifying three phases in the development of North American organizations: market insertion, from 1994 to mid-2002; growth and diversification, from mid-2002 to 2007; and a larger scale offer, from the end of 2007 until today. Carsharing continues to be of interest to researchers, in particular from the angle of impact on motorization (Cervero et al, 2007;Martin et al, 2010), the multimodal aspect of the phenomenon (Nobis, 2006(Nobis, , 2007, its effects on the environment (Alexandre, 2010;Firnkorn and Müller, 2011), and user behaviour (Jemelin and Louvet, 2007;Morency et al, 2012;Costain et al, 2012) or its potential in Shanghai (Wang et al, 2012). The present article examines the geographical and socio-economic factors underlying the deployment of the carsharing service in Québec City so as to determine their relative weight using a statistical model.…”
Section: Introductionmentioning
confidence: 99%